The End-User's Satisfaction of Public Space in Dataran Cendekia UiTM Shah Alam - Yaman, Rostam; Ismail, Farrah Zuhaira; Ahmad, Noraini (International Journal of Sustainable Construction Engineering and Technology, 2021)
Successful public space should meet the needs of all people in different social classes, ages, genders, ethnicities and backgrounds. These substantially beneficial spaces provide physical, social and psychological comfort for public user. Dataran Cendekia UiTM Shah Alam shows lacks of satisfactorily public open spaces that meet user needs. The main question raised in this research is "what are the public user satisfaction and the quality of public space towards a better public space?" This research aims to investigate the quality and public's satisfaction towards a public space at Dataran Cendekia UiTM Shah Alam. The research employed a set of questionnaires that involves quantitative approach to achieve a precise data collection and information. The finding shows that the public facilities, activities, landscape and maintenance plays a huge and significant role in attracting people to the public open space. The research disclosed that the public users are only having passive activities in the public spaces. The results showed that the lack of quality in facilities and also lack of interesting activities affect social experiences in public space. Furthermore, the lack of proper shades. In summary, the physical factors, social activities and events, inclusiveness and social interactions, and design features are the public space contributing factors to the creation of a successful public open space.